2011
DOI: 10.5586/asbp.2005.019
|View full text |Cite
|
Sign up to set email alerts
|

Carex secalina (Cyperaceae), a species critically endangered in Europe: from propagule germination to propagule production

Abstract: ABCTRACTThe size and reproduction ability of the three field populations of Carex secalina Willd. ex Wahlenb. have been assessed. In the parallel garden study selected traits from the life history of the species have been studied, such as age at first reproduction, fertility, the size of seeds, their germination ability and size of seedlings. The populations of C. secalina discovered in Poland in 2000 are characterised by small abundance and small area. All individuals from the three populations in the garden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…As we have previously found, the species has occurred on highly salt-affected solontchak and solonetz soils, where electric conductivity reached values of 1.7-6.2 mS × cm −1 [66]. On the other hand, Žukowski et al [58] pointed out that enlarging of C. secalina areas in Poland could be restricted by inhibition of germination and seedling survival due to high salinity of soil. But the authors noted that this hypothesis needs verification.…”
Section: Distribution In the Czech Republic And In Slovakiamentioning
confidence: 94%
See 1 more Smart Citation
“…As we have previously found, the species has occurred on highly salt-affected solontchak and solonetz soils, where electric conductivity reached values of 1.7-6.2 mS × cm −1 [66]. On the other hand, Žukowski et al [58] pointed out that enlarging of C. secalina areas in Poland could be restricted by inhibition of germination and seedling survival due to high salinity of soil. But the authors noted that this hypothesis needs verification.…”
Section: Distribution In the Czech Republic And In Slovakiamentioning
confidence: 94%
“…The authors found a positive correlation between population size of the species and grazing intensity. Other significant factors enhancing the germination efficiency were diaspore trampling into the ground by animal hooves, and the high generative reproduction abilities of individuals (individuals producing large amounts of seeds) [58].…”
Section: Distribution In the Czech Republic And In Slovakiamentioning
confidence: 99%
“…Moreover, our studies on sedge seed germination have shown a high importance of life history traits (Øukowski et al 2005;Lembicz et al 2010). Our experiment under controlled conditions of a garden allowed to observe the effect of mother plant age on the development of seeds and seedlings of Carex secalina.…”
Section: Factors Controlling Germinationmentioning
confidence: 99%
“…In winter, the aboveground parts of plants die and form necromass. In subsequent years, renewed vegetative growth begins in April [22].…”
Section: Species Studiedmentioning
confidence: 99%
“…The species studied was the sedge Carex secalina because it is a perennial, monoecious species, easy to cultivate, and its individuals are clearly distinguishable and do not reproduce vegetatively [22].…”
Section: Introductionmentioning
confidence: 99%